Disaster risk index on disaster management budgeting: Indonesia’s national data set - Nurhayati Haris; Andi C. Furqan; Abdul Kahar; Fikry Karim (Jàmbá, 2023)
This study analysed Indonesian local government budgeting model based on the Disaster Risk Index (DRI). This study used a sample of local governments in Indonesia consisting of provincial, regency and municipality levels, especially for 2015–2019 data with a final sample of 2609 observations. The results of the analysis and testing showed that most of the Indonesian local governments fall into the high category in the DRI. The DRI has a positive effect on the Disaster Response Emergency Fund (DREF). The results were robust to the differences in DRI measurements, both using scores and DRI categories. This study also found that the DRI has been used as the basis for budgeting regional expenditures. The budget was allocated in disaster-related public procurements such as public service, housing, public facilities and public health. The budgeting for the implementation of economic and social functions was not influenced by the DRI. Instead, the DRI was found to have a negative effect on the implementation of environmental functions. The findings showed that in general, DRI has been used as the basis for budgeting for regional disaster management, but it is still limited to functions related to disaster emergency response. The budgeting of functions related to the prevention stage has not been optimally carried out, especially by mitigating natural hazards through strengthening the quality of the environment.